POLITIK HUKUM TERHADAP PEDAGANG KAKI LIMA DARI PERSPEKTIF UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Suardin, Yohannes (Fiat Iustitia : Jurnal Hukum, 2020)
The existence of the 1945 Constitution of the State of the Republic of Indonesia has been quite clear that it also encompasses marginal communities, one of which is street vendors, although explicitly it cannot be read. This is already apparent from one of the national goals contained in the 4th paragraph Opening of the Constitution of the Republic of the Republic which states "promoting public welfare". However, it is implicit in the provisions of Article 34 of the 1945 Constitution of the Republic of Indonesia in particular paragraph (2) of the state developing a social security system for all people and empowering people who are weak and unable to comply with human dignity. Promote general welfare (goodness) called bonum commune, including the marginal community, especially the street vendors who are specifically analyzed in this article. Thus, legal politics towards street vendors from the perspective of the 1945 Constitution of the Republic of Indonesia is adequate, and what must be improved is the political will of partiality towards street vendors.